2004
DOI: 10.1016/s0002-9440(10)63774-1
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase-Aβ Complexes Are More Toxic than Aβ Fibrils in Rat Hippocampus

Abstract: Neuropathological changes generated by human amyloid-beta peptide (Abeta) fibrils and Abeta-acetylcholinesterase (Abeta-AChE) complexes were compared in rat hippocampus in vivo. Results showed that Abeta-AChE complexes trigger a more dramatic response in situ than Abeta fibrils alone as characterized by the following features observed 8 weeks after treatment: 1). amyloid deposits were larger than those produced in the absence of AChE. In fact, AChE strongly stimulates rat Abeta aggregation in vitro as shown by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(47 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…Experimental evidences illustrate that AChE accelerates aggregation of Ab peptide and formation of Ab-AChE complex at the synaptic region of hippocampus leading to DOI: 10.3109/13880209.2015.1017886 neuronal degeneration (Dinamarca et al, 2010;Reyes et al, 2004). Symptomatic treatment for AD involves potentiation of cholinergic activity through the inhibition of AChE (Rahman & Choudhary, 2001).…”
Section: Acetylcholinesterase and Butyrylcholinesterase Inhibitory Acmentioning
confidence: 99%
“…Experimental evidences illustrate that AChE accelerates aggregation of Ab peptide and formation of Ab-AChE complex at the synaptic region of hippocampus leading to DOI: 10.3109/13880209.2015.1017886 neuronal degeneration (Dinamarca et al, 2010;Reyes et al, 2004). Symptomatic treatment for AD involves potentiation of cholinergic activity through the inhibition of AChE (Rahman & Choudhary, 2001).…”
Section: Acetylcholinesterase and Butyrylcholinesterase Inhibitory Acmentioning
confidence: 99%
“…[11] Because the adhesion function of AChE to Ab is located at the peripheral anionic site (PAS), [12] inhibitors that are able to bind both the catalytic active site (CAS) and PAS are of particular interest in AD, as they can simultaneously improve memory and slow the rate of amyloid degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing a tether of six methylene units (5,8,11,16, and 21) showed shorter distances to PAS residues, indicating improved p-p stacking interactions. For instance, hybrid 11 (n = 6) showed better stabilizing interactions with PAS residues than its counterpart 10 (n = 5, Table 3).…”
mentioning
confidence: 99%
“…Aβ peptides deposition induces cholinergic denervation in AD [38]. Moreover, studies have shown that AChE could precipitate Aβ plaques deposition in the AD patients’ brain [39-41]. Somani et al [42] showed that chemical and physical stressors decrease choline acetyltransferase and AChE enzymes in the brain.…”
Section: Discussionmentioning
confidence: 99%